As metodologias para o ensino de história no ensino fundamental utilizadas no ensino fundamental na Escola Estadual Técnica Olavo Bilac - (:unkn) unknown (Universidade Federal do Pampa, 2017)
This course completion work aims to approach the methodologies used by the teachers of the Olavo Bilac Technical School in the area of History. It is based on the understanding that teaching methodologies contribute to quality education. It is necessary to rethink teaching as something innovative and that makes learning pleasant. It is known that to obtain quality education it is necessary investment and valorization of the professional. It is also necessary that educators understand the dimension of their performance in the process of teaching learning. Thus, it is expected that educators are not simply breeders of knowledge. These should provide the student with quality teaching-learning. They should awaken in the student the pleasure in learning. Firstly, the study made a historical rescue on the education and teaching of History in Brazil, in order to know the historical context about education in Brazil and the problems faced over the years. Then there is the discussion about the role of teacher and student in teaching history. There was also reflection on the importance of the methodologies, the teacher, the motivation of the student in the classroom, not forgetting to make a brief but important analysis about Elementary School having the discipline of History as part of this analysis. To construct the analysis two questionnaires were applied. Based on the empirical analysis, where students answered on: the methodologies used by teachers, the resources used in classes, if there is content mastery. Teachers responded in relation to academic training and how history classes are taught. The questionnaires were applied at the Olavo Bilac Technical School, in the 8th and 9th grade classes and for two teachers, trained in the History area. The results of the interviews were transformed into graphs and from the analisedas responses. With the correct analysis, it was realized that the school aims to encourage teachers to adopt methodologies that provide a way out of fragmented and traditional teaching. In this context, one can see the importance of the classroom educator acting in order to break paradigms and innovative methodological practices with the aid of meaningful learning to provide the conditions for the construction of knowledge.
Keywords: Ensino – Metodologia; Aprendizagem; História - Estudo e ensino; Teaching-Methodology; CNPQ::CIENCIAS HUMANAS